Impact of mode of transport on the outcome of extramural newborns in a tertiary care centre - Thenmozhi, M.; Sathya, J. (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal transport system in our country is a major gap in holistic newborn care and acute neonatal physiology deranged during neonatal transport which adversely affects the mortality and morbidity of sick newborns. To determine the effect of mode of transport on outcome of extramural newborns. To determine the effect of mode of transport on extramural newborns outcome at the level of tertiary care center. Methods: This is a prospective cohort study carried out in chengalpattu medical college and hospital, NICU over a period of 6 months. Inclusion criteria were all admitted extramural babies, readmitted intramural babies and those babies died while transport. Exclusion criteria were those babies born in the institution of study. A predesigned and tested proforma was used to record the required information for the study at the time of admission. Data was analysed and tabulated, for analysis of data software STATISTIX was used. Results: Out of 490 newborns 11% were died, 84% were discharged and 2.45% were gone against medical advice. About the mode of transport was 60% by Ambulances, 10.6% by Auto, 22% by Bus and 6.8% by Car. Conclusions: The study concludes that even though the mode of transport accompanied by a health personnel no difference in the outcome of babies. So, we suggest well trained and equipped transport system to improve the outcome.